IMPROVEMENT OF THE MANAGEMENT SYSTEM BETWEEN THE LEADER AND FOLLOWERS: RESOLUTION OF LABOR CONFLICTS - Y. Kulikova (Вестник Северо-Кавказского федерального университета, 2022)
Interest in leadership arose in ancient times. The phenomenon of leadership over the centuries has worried the minds of many researchers. This article is devoted to improving the management system in the relationship of the leader and followers, as a way to resolve labor conflicts, management styles are considered. The article gives a brief description of the psychological qualities and personality traits. And also considered the weaknesses and strengths of leadership. In the article, the author also noted leadership skills, as well as ways to influence employees.